2021
DOI: 10.4049/jimmunol.2000862
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K8 Regulates Cox-2–Mediated Prostaglandin E2 Production in the Lung and Suppresses Pulmonary Inflammation and Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by exuberant deposition of extracellular matrix components, leading to the deterioration of lung architecture and respiratory functions. Profibrotic mechanisms are controlled by multiple regulatory molecules, including MAPKs, in turn regulated by multiple phosphorylation cascades. MAP3K8 is an MAPK kinase kinase suggested to pleiotropically regulate multiple pathogenic pathways in the context of inflammation and cancer; however, a possible role in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In addition, inspecting MAP3K8 in higher resolution data via the explorer’s Map to single cell data feature instantly revealed an “enrichment” of gene’s expression in monocytic-lineage cells. These findings were further validated in the bleomycin-induced animal model of pulmonary fibrosis, where genetic deletion of MAP3K8 was shown to exacerbate the modeled disease 30 . All results impelling us to wet lab examination of MAP3K8 expression during lung fibrosis can be replicated using the Example button of Gene explorer and then filtering the DEG statistics table for lung tissue and IPF_vs_Ctrl comparisons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, inspecting MAP3K8 in higher resolution data via the explorer’s Map to single cell data feature instantly revealed an “enrichment” of gene’s expression in monocytic-lineage cells. These findings were further validated in the bleomycin-induced animal model of pulmonary fibrosis, where genetic deletion of MAP3K8 was shown to exacerbate the modeled disease 30 . All results impelling us to wet lab examination of MAP3K8 expression during lung fibrosis can be replicated using the Example button of Gene explorer and then filtering the DEG statistics table for lung tissue and IPF_vs_Ctrl comparisons (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Fibromine’s Gene explorer enables interrogation of single/multiple gene expression motifs (consistently recurring DEA results across same/similar experimental conditions), a very useful feature to validate wet laboratory findings and quickly deepen novel hypotheses formation. For example, following leads from cancer and inflammatory diseases, our laboratory has used a primary version of Fibromine’s Gene explorer to discover that based on the three larger IPF_vs_Ctrl bulk lung datasets, MAP3K8 is down-regulated in IPF patients’ lungs 30 . In addition, inspecting MAP3K8 in higher resolution data via the explorer’s Map to single cell data feature instantly revealed an “enrichment” of gene’s expression in monocytic-lineage cells.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple lines of evidence have recently implicated Tpl2 in restraining fibrotic responses, both in intestinal myofibroblast-mediated fibrosis in the gut [ 23 ] and in bleomycin-induce lung fibrosis [ 22 ]. Because pulmonary fibrosis can impair lung function during influenza infection [ 40 ], we assessed whether Tpl2 protects against influenza-induced lung injury by inhibiting pulmonary fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Given the cell-type and stimulus-specific nature of Tpl2 [ 9 ], other radioresistant cell types, such as stromal cell populations, including endothelial cells and myofibroblasts also need to be considered. Previous studies have shown important roles for Tpl2 in intestinal [ 23 ] and lung myofibroblast [ 22 ] and lung endothelial cells [ 50 ]. However, whether and how Tpl2 functions in these cell types to induce protective antiviral responses is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation